SINTESIS DAN KARAKTERISASI HIDROGEL KITOSAN-LIDAH BUAYA (Aloe vera)-LENDIR BEKICOT (Achatina fulica) - Emelia Amanda Agustin; Sari Edi Cahyaningrum (Unesa Journal of Chemistry, 2026)
Hydrogels are topical formulations designed to be more practical in promoting faster wound healing. Hydrogels must possess characteristics such as biocompatibility, non-toxicity, sensitivity to the physiological environment, and good flexibility. These characteristics open up opportunities for hydrogels to be applied in biomedicine through combinations of materials that have synergistic effects. This study was conducted to synthesize hydrogels by combining chitosan, aloe vera, and snail mucus. In this study, hydrogels were synthesized with varying additions of aloe vera at 5, 10, and 15% (w/w), followed by physical and chemical characterization. The results showed that increasing the amount of aloe vera added increased the spreadability and decreased the adhesion of the hydrogel. The characterization test results showed a spreadability range of 5,07–5,34 cm and an adhesion time of 16–44 seconds.